Reliability Centered Maintenance as a basis for establishing improvement options for steel heat treatment equipment - Aguilera-Órdenes, Gonzalo; Amador-Cáceres, Belkys (EASI: Engineering and Applied Sciences in Industry, 2024)
The steel ball plant for mining grinding works to achieve high standards by optimizing processes to reduce production costs, meet demand, and improve market competitiveness. The company's need to add value to its processes through increased availability and reliability of the steel heat treatment equipment is the driving force behind this work. Steel quenching is essential for the quality of steel balls for mining grinding, as it is in this stage that the balls acquire the mechanical properties demanded by the market. Therefore, the objective of this work is to establish improvement options for steel heat treatment equipment based on the application of the Reliability-Centered Maintenance methodology. Through the information of each piece of equipment, obtained from catalogs, manuals, and the personnel who know and work with each one, the application of the methodology was founded, identifying for each piece of equipment the functions, functional failures, failure modes, and effects and consequences of the failure modes. This process is fundamental to identifying those failure modes that, beyond requiring a maintenance strategy, necessitate a change in design, process, or procedure. These changes are directly associated with the proposed improvement options, which aim to eliminate or mitigate the respective failure modes.
Keywords: improvement options; reliability-centered maintenance; steel heat treatment equipment; steel balls for mining